Are Patients Who Undergo the Latarjet Procedure Ready to Return to Play at 6 Months? A Multicenter Orthopaedic Outcomes Network (MOON) Shoulder Group Cohort Study. Issue 4 (March 2020) - Frantz, Travis L.; Everhart, Joshua S.; Cvetanovich, Gregory L.; Neviaser, Andrew; Jones, Grant L.; Hettrich, Carolyn M.; Wolf, Brian R.; Baumgarten, Keith M.; Bollier, Matthew J.; Bravman, Jonathan T.; Kuhn, John E.; et al.
Background: The Latarjet procedure is growing in popularity for treating athletes with recurrent anterior shoulder instability, largely because of the high recurrence rate of arthroscopic stabilization, particularly among contact athletes with bone loss. Purpose: (1) To evaluate return of strength and range of motion (ROM) 6 months after the Latarjet procedure and (2) to determine risk factors for failure to achieve return-to-play (RTP) criteria at 6 months. Study Design: Case-control study; Level of evidence, 3. Methods: A total of 65 athletes (83% contact sports, 37% overhead sports; mean ± SD age, 24.5 ± 8.2 years; 59 male, 6 female) who enrolled in a prospective multicenter study underwent the Latarjet procedure for anterior instability (29% as primary procedure for instability, 71% for failed prior stabilization procedure). Strength and ROM were assessed preoperatively and 6 months after surgery. RTP criteria were defined as return to baseline strength and <20° side-to-side ROM deficits in all planes. The independent likelihood of achieving strength and motion RTP criteria at 6 months was assessed through multivariate logistic regression modeling with adjustment as needed for age, sex, subscapularis split versus tenotomy, preoperative strength/motion, percentage bone loss, number of prior dislocations, preoperative subjective shoulder function (American Shoulder and Elbow Surgeons and Western Ontario Shoulder Instability Index percentage), and participation in contact versus overhead sports. Results: Of the patients, 55% failed to meet ≥1 RTP criteria: 6% failed for persistent weakness and 51% for ≥20° side-to-side loss of motion. There was no difference in failure to achieve RTP criteria at 6 months between subscapularis split (57%) versus tenotomy (47%) ( P = .49). Independent risk factors for failure to achieve either strength or ROM criteria were preoperative American Shoulder and Elbow Surgeons scores (per 10-point decrease: adjusted odds ratio [aOR], 1.61; 95% CI, 1.14-2.43; P = .006), Western Ontario Shoulder Instability Index percentage (per 10% decrease: aOR, 0.61; 95% CI, 0.38-0.92; P = .01), and a preoperative side-to-side ROM deficit ≥20° in any plane (aOR, 5.01; 95% CI, 1.42-21.5; P = .01) or deficits in external rotation at 90° of abduction (per 10° increased deficit: aOR, 1.64; 95% CI, 1.06-2.88; P = .02). Conclusion: A large percentage of athletes fail to achieve full strength and ROM 6 months after the Latarjet procedure. Greater preoperative stiffness and subjective disability are risk factors for failure to meet ROM or strength RTP criteria.